2009
DOI: 10.3329/jhpn.v26i3.1903
|View full text |Cite
|
Sign up to set email alerts
|

Spousal Violence in Bangladesh: A Call for a Public-health Response

Abstract: Spousal violence against women is a serious public-health issue. Although there is a growing body of literature on this subject, there are still many unanswered questions regarding the prevalence of this violence, the risk factors, the consequences, and how to address the issue. The purpose of this literature review is to organize and synthesize the empirical evidence on spousal violence against women in Bangladesh and to provide direction for both researchers and practitioners for future work in this area. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Most research on IPV globally is based on women’s reported exposure, with little known about the reasons for men’s perpetration (Johnston & Naved, 2008; Sambisa et al, 2010). Limited evidence from poorer settings suggests that violence in childhood and inequitable local gender norms may synergistically elevate men’s risks of perpetrating IPV, but these risk factors have not been studied together (Abramsky et al, 2011; Ackerson & Subramanian, 2008; Dalal, Lee, & Gifford, 2012; Heise, 2011; Jewkes, 2002).…”
Section: Men’s Perpetration Of Ipvmentioning
confidence: 99%
“…Most research on IPV globally is based on women’s reported exposure, with little known about the reasons for men’s perpetration (Johnston & Naved, 2008; Sambisa et al, 2010). Limited evidence from poorer settings suggests that violence in childhood and inequitable local gender norms may synergistically elevate men’s risks of perpetrating IPV, but these risk factors have not been studied together (Abramsky et al, 2011; Ackerson & Subramanian, 2008; Dalal, Lee, & Gifford, 2012; Heise, 2011; Jewkes, 2002).…”
Section: Men’s Perpetration Of Ipvmentioning
confidence: 99%
“…Bangladesh has been experiencing an increase in domestic violence (Islam et al., 2014). Research has shown that suicidal ideation was more common among abused women in Bangladesh (Johnston & Naved, 2008; Naved & Akter, 2008). The authors recommended initiatives to curb domestic violence against women (Naved & Akter, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Violence against women is a global public health issue [1]. Intimate partner violence is the most common kind of violence, and is a significant public health issue [2]. Although previously intimate partner violence (IPV) was considered a private family matter, however, in the last 30 years, it has been recognized as a significant social concern that includes physical and mental health consequences [3].…”
Section: Introductionmentioning
confidence: 99%